When countries do not do what they say: Systematic discrepancies between exchange rate regime announcements and de facto policies - Julia Bersch; Ulrich H. Klüh (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
We study the apparent disconnect between what countries announce to be their exchange rate regime and what they de facto implement. Even though discrepancies between announcements and de facto polices are frequent, there is a lack of understanding of actual patterns and underlying reasons. We contribute to the literature by identifying a number of robust stylized facts by means of an in-depth analysis of a large cross-country dataset. A key insight is that countries that operate under intermediate de facto regimes tend to announce fixed or flexible exchange rate regimes. The exact nature of deviations is related to country characteristics such as trade structure, financial development, and financial openness. Furthermore, regime discrepancies have followed secular trends, which are most likely related to financial globalization and changes in monetary policy design.
urn:nbn:de:bvb:19-epub-2072-1
Keywords: F31; F33; F41; 330; Exchange rate regimes; de facto versus de jure; exchange rate policy; Wechselkurspolitik; Wechselkurssystem; Staatliche Information; Außenwirtschaftspolitik; Geldpolitik; Globalisierung; Vergleich; Welt